RASA AMAN, PROFESIONAL DAN KINERJA PELAYANAN - Ronny Defrika (Universitas Riau, 2015)
Security, Professionalism and Service Performance. The purpose of this study was to describe and to determine the safety, professionalism auction service employees on organizational performance Bengkalis Procurement Unit. This research is a quantitative method, the population is bidders who numbered 256 participants and 72 samples using random sampling populasional. Data was collected by questionnaire. The results using a variable sense of safety and professionalism in partial positive and significant influence together (simultaneously) significantly affects the performance of the ULP, with a 95% confidence level. Furthermore, the results of data analysis showed that the coefficient of determination (R2) of the model is 0764, which means that 76.4% of independent variables (a sense of security and professionalism) is able to explain the dependent variable (performance ULP) and the remaining 23.6% is influenced by variables other outside variables in this study